GENERAL CONCEPT OF CHRONIC TONZILLITIS. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Chronic tonsillitis, which is common in the field of otorhinolaryngology, is one of the most common diseases of the upper respiratory tract. Regarding the cause of the disease, according to various epidemiological data, this disease occurs in approximately 5-15% of the population, and in children up to 20-30%. This condition is one of the urgent problems encountered in medical practice